Mathematical modelling of polymer electrolyte membrane fuel cell and fuzzy-based intelligent controllers for performance enhancement. (July 2019) - Sreedharan, Dhanya; Paul, Varghese; Thottungal, Rani
Abstract: We present the results of mathematical modelling of a 500 W polymer electrolyte membrane fuel cell implemented in Matlab/Simulink, and of the design of intelligent controllers such as fuzzy logic controllers (FLCs) and adaptive neuro-fuzzy controllers (ANFCs). The controllers regulate anode-side pressure, cathode flow, pressure difference, and humidity. Regulation of the anode-side pressure maintains the desired anode-cathode pressure differential. The net controller actions deliver the rated power while operating in a safe regime. The ANFC is shown to be more successful as compared to the FLC in attaining the optimum values of the cathode pressure, flow rate, and the flow rate of water injected from the humidifier at 20 A, which gives a rated power of 500 W. The novelty of the work is the simultaneous operation of these controllers in regulating these critical parameters to achieve the desired electrical performance. The efficiency of the controllers is very important for the hardware implementation and ease of real-time operation.